2017
DOI: 10.18632/oncotarget.21272
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-212/ABCG2-axis contributes to development of imatinib-resistance in leukemic cells

Abstract: BCR-ABL-independent resistance against tyrosine kinase inhibitor is an emerging problem in therapy of chronic myeloid leukemia. Such drug resistance can be linked to dysregulation of ATP-binding cassette (ABC)-transporters leading to increased tyrosine kinase inhibitor efflux, potentially caused by changes in microRNA expression or DNA-methylation. In an in vitro-imatinib-resistance model using K-562 cells, microRNA-212 was found to be dysregulated and inversely correlated to ABC-transporter ABCG2 expression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 62 publications
(74 reference statements)
2
21
0
Order By: Relevance
“…The upregulation of MDR proteins leads to excessive efflux of structurally and mechanistically diverse drugs and is an important mechanism of drug resistance ( 31 ). BCRP has been reported to mediate the resistance of many unrelated anticancer drugs, including doxorubicin ( 23 ), etoposide ( 32 ), imatinib ( 33 ), methotrexate ( 34 ), and mitoxantrone ( 23 , 35 ), among others ( 16 , 17 , 31 ). In keeping with this, our results showed the TAK-243–resistant BEND3 -knockout cells were cross-resistant to the known BCRP substrate mitoxantrone.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of MDR proteins leads to excessive efflux of structurally and mechanistically diverse drugs and is an important mechanism of drug resistance ( 31 ). BCRP has been reported to mediate the resistance of many unrelated anticancer drugs, including doxorubicin ( 23 ), etoposide ( 32 ), imatinib ( 33 ), methotrexate ( 34 ), and mitoxantrone ( 23 , 35 ), among others ( 16 , 17 , 31 ). In keeping with this, our results showed the TAK-243–resistant BEND3 -knockout cells were cross-resistant to the known BCRP substrate mitoxantrone.…”
Section: Discussionmentioning
confidence: 99%
“…Using prediction by bioinformatics, it was discovered that the miR-222 sequence is closely associated with ALDH1, and may possibly be an upstream miRNA that regulates ALDH1 expression. miR-222 may cut the mRNA of ALDH1 to inhibit its translation (32). Regulation by miRNA promotes the upor downregulation of mRNA and plays an important role in the occurrence and development of diseases (33).…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that MRP1-3 lead to resistance to hydrophobic and anionic compounds, including several natural compounds, whereas MRP4, MRP5 and MRP8 efflux cyclic nucleotides (13,14). BCRP, a ubiquitous ABC transporter, has been shown to transport nucleoside drugs and nucleoside-monophosphate derivatives of clinically relevant nucleoside drugs (15,16). Moreover, these ABC transporters are highly expressed in various human cancer types and are closely associated with poor prognosis (17,18).…”
Section: Effect Of Sodium Butyrate On Abc Transporters In Lung Cancermentioning
confidence: 99%